Relación entre la solvencia y la rentabilidad de la corporación Cementos Pacasmayo S.A.A. periodo 2018 – 2024 - Trauco Ricopa, Adriana Magnolya (2025)
This study explored the relationship between solvency and profitability at Cementos Pacasmayo S.A.A. over the period 2018–2024, aiming to uncover how financing choices and working‐capital management impact net margins, Return on Assets (ROA), and Return on Equity (ROE). Adopting a quantitative, non-experimental, longitudinal design, the research conducted a full census of audited quarterly financial statements. Descriptive statistics, multiple linear regression analyses, and Spearman correlation tests were employed to examine one general hypothesis and three specific hypotheses. Findings demonstrated a moderate, positive association between solvency and overall profitability (ρ = 0.4641; p = 0.042), as well as direct links between the current ratio and net profit margin (ρ = 0.5241; p = 0.033), debt ratio and ROA (ρ = 0.4662; p = 0.042), and interest coverage and ROE (ρ = 0.3532; p = 0.036). The results confirm that maintaining prudent liquidity and measured leverage enhances asset efficiency and shareholder value, provided that debt costs remain below asset returns. Moreover, the study highlights the importance of flexible debt terms and effective receivables and inventory policies to withstand cyclical fluctuations in the cement industry. In sum, this research offers robust empirical evidence on balancing liquidity, leverage, and profitability in cyclical sectors and lays the groundwork for more resilient and adaptive financial strategies.